Annual precipitation and daily extreme precipitation distribution: possible trends from 1960 to 2010 in urban areas of China. Issue 1 (1st January 2019) - Li, Weiyue; He, Xiaogang; Scaioni, Marco; Yao, Dongjing; Mi, Chunrong; Zhao, Jing; Chen, Yu; Zhang, Kaihang; Gao, Jun; Li, Xin
Abstract: With global warming, precipitation events are often prone to intensify in some regions. Understanding the changing characteristics of annual and daily extreme precipitation as well as the underlying mechanisms plays an import role for early warning of precipitation-induced disaster (e.g. floods, landslides) and water resources management, especially in densely populated urban areas. In this study, we investigate the long-term trend of annual and daily extreme precipitation in China during 1960–2010 based on daily observations from 539 meteorological stations, and the land cover map with impervious information. We find an overall increasing trend in annual and daily extreme precipitation, particularly in South-East and North-West of China. Moreover, 157 stations located in metropolitan regions experience higher increasing trends of daily extreme precipitation, particularly in Shanghai and Guangzhou metropolitan areas. It is noted that the central urban area of one metropolitan region may have significantly higher increasing trends of daily extreme precipitation than corresponding surrounding areas.